Effect of thermal aging on ductile-brittle transition temperature of modified 9Cr-1Mo steel evaluated with reference temperature approach under dynamic loading condition - Sathyanarayanan S.; Basu J.; Moitra A.; Sasikala G.; Singh V. (My University, 2025)
The effect of thermal aging on the ductile-brittle transition behavior has been assessed for a modified 9Cr-1Mo steel (P91) using the reference temperature approach under dynamic loading condition (T 0 dy). The steel in normalized and tempered (NT) condition and in different levels of subsequent cold work (CW) was subjected to thermal aging at temperatures of 873 K and 923 K (600 C and 650 C) for 5000 and 10,000 hours. For the NT and all the cold work conditions of the starting material, a drastic increase in T 0 dy has been noticed after aging at 923 K (650 C) for 10,000 h. A moderate increase was observed for the NT steel aged at 873 K (600 C) for 5000 hours and for the 10 pct CW steel aged at 873 K (600 C) for 10,000 h. A detailed transmission electron microscope (TEM) study of the embrittled materials aged at 923 K (650 C)/10,000 hours and 873 K (600 C)/10,000 hours has indicated presence of hexagonal Laves phase of Fe2(Mo,Nb) type with different size and spatial distributions. The increase in the T 0 dy is attributed to the embrittling effect of a network of Laves phase precipitates along the grain boundaries. © 2013 The Minerals, Metals & Materials Society and ASM International.